2013
DOI: 10.1080/02699931.2013.823381
|View full text |Cite
|
Sign up to set email alerts
|

Preferring familiar emotions: As you want (and like) it?

Abstract: Do people want to feel emotions that are familiar to them? In two studies, participants rated how much they typically felt various emotions (i.e., familiarity of the emotion) and how much they generally wanted to experience these emotions. We found that, in general, people wanted to feel pleasant emotions more than unpleasant emotions. However, for both pleasant and unpleasant emotions, people more (vs. less) familiar with an emotion also wanted to experience it more. Links between the familiarity of an emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 25 publications
3
39
0
Order By: Relevance
“…Consistent with suggestions made by Ford and Tamir (2014), our exploratory findings showed that the emotions people considered useful were also the emotions they generally wanted to experience in their everyday lives (positive emotions: r = .30, p < .001; negative emotions: r = .46, p < .001). Consistent with suggestions made by Ford and Tamir (2014), our exploratory findings showed that the emotions people considered useful were also the emotions they generally wanted to experience in their everyday lives (positive emotions: r = .30, p < .001; negative emotions: r = .46, p < .001).…”
Section: Exploratory Analysessupporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with suggestions made by Ford and Tamir (2014), our exploratory findings showed that the emotions people considered useful were also the emotions they generally wanted to experience in their everyday lives (positive emotions: r = .30, p < .001; negative emotions: r = .46, p < .001). Consistent with suggestions made by Ford and Tamir (2014), our exploratory findings showed that the emotions people considered useful were also the emotions they generally wanted to experience in their everyday lives (positive emotions: r = .30, p < .001; negative emotions: r = .46, p < .001).…”
Section: Exploratory Analysessupporting
confidence: 86%
“…What is the relationship between emotion utility beliefs and general emotional preferences?. Consistent with suggestions made by Ford and Tamir (2014), our exploratory findings showed that the emotions people considered useful were also the emotions they generally wanted to experience in their everyday lives (positive emotions: r = .30, p < .001; negative emotions: r = .46, p < .001). The exploratory findings of Study 1 led us to focus our confirmatory Study 2 on people's beliefs about the utility of emotions and how these beliefs varied by self-control type and trait self-control, and to leave the question of why people believe that certain emotions are helpful or unhelpful for their self-control success for future research.…”
Section: Exploratory Analysessupporting
confidence: 86%
“…However, people also seek emotions that promote other benefits, regardless of immediate pleasure or pain (Parrott, 1993;Tamir, 2015). Likewise, people who experience more (vs. less) anger or fear are more motivated to experience anger or fear, respectively (Ford & Tamir, 2014). People with low self-esteem are less motivated to repair sad moods, partly because such moods are familiar to them (Wood et al, 2009).…”
Section: Emotion-regulation Goals In Depressionmentioning
confidence: 99%
“…Meanwhile, people higher in Neuroticism tend to experience more negative emotions, such as anger (Watson & Clark, 1992). Most research suggests that people prefer trait-consistent states (Costa & McCrae, 1980;Ford & Tamir, 2014;Lucas, Le, & Dyrenforth, 2008;Tamir, 2005Tamir, , 2009. For example, extraverts report more strongly wanting to experience positive emotions (e.g., Larsen & Ketelaar, 1989;Tsai, Knutson, & Fung, 2006), and individuals higher in Neuroticism want to feel more negative emotions, such as worry when performing a demanding task (e.g., taking a test; Kämpfe & Mitte, 2009;Tamir, 2005;cf.…”
Section: Hedonic Goalsmentioning
confidence: 99%